2009
DOI: 10.4161/psb.4.6.8847
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic alkalinization is a common and early messenger preceding the production of ROS and NO during stomatal closure by variable signals, including abscisic acid, methyl jasmonate and chitosan

Abstract: Stomata are unique that they sense and respond to several internal and external stimuli, by modulating signaling components in guard cells. The levels of reactive oxygen species (ROS), nitric oxide (NO) and cytosolic calcium (Ca 2+ ) increase significantly during stomatal closure by not only plant hormones [such as abscisic acid (ABA) or methyl jasmonate (MJ)] but also elicitors (such as chitosan). We observed that cytosolic alkalinization preceded the production of ROS as well as NO during ABA induced stomata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…Although cytosolic alkalization in guard cells has been shown to occur early in ABA-and MJ-induced H 2 O 2 production and stomatal closure [27,61], it is unknown whether cytosolic alkalization is a causal factor for H 2 O 2 production during darkness-induced stomatal closure. To answer this question, the effect of butyric acid on darkness-induced H 2 O 2 production in guard cells was determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cytosolic alkalization in guard cells has been shown to occur early in ABA-and MJ-induced H 2 O 2 production and stomatal closure [27,61], it is unknown whether cytosolic alkalization is a causal factor for H 2 O 2 production during darkness-induced stomatal closure. To answer this question, the effect of butyric acid on darkness-induced H 2 O 2 production in guard cells was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Effectors that decrease the cytosolic pH (auxin, fusicoccin) open stomata [28], while those that raise the cytosolic pH (ABA and MJ) result in stomatal closure [27,32]. Cytosolic alkalization has been reported to precede the production of reactive oxygen species during ABA-and MJ-induced stomatal closure [27,61]. However, whether S1P affects guard cell cytosolic pH to regulate stomatal movement is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ABA-induced stomatal closing also partly depends on cytosolic alkalization, which precedes production of both ROS and NO, and appears to promote increased NO levels (Irving et al, 1992;Gonugunta et al, 2009). This process requires function of OST1, one of the SnRK2s acting in the core signaling pathway, and is also both induced by increased [Ca 2+ ] cyt and regulates oscillations in [Ca 2+ ] cyt (Islam et al, 2010).…”
Section: +mentioning
confidence: 99%
“…Although it is well known that NO interacts with ABA, ET, MeJA to control guard cell signaling in response to various environmental stresses [140,141], only few reports are available with regard to NO, ET, and ABA cross talk in stomatal regulation under UV-B stress [142]. Studies involving Lactuca sativa seedlings showed that exogenous NO supply (using SNP as a NO donor) prevented UV-B induced inhibition of GA and IAA synthesis [143].…”
Section: No-phytohormone Cross Talk Under Other Abiotic Stressesmentioning
confidence: 99%